Communication strategy of the East Kalimantan government on tourism development - Anwar; Surya, Iman; Resmawan, Erwin (Faculty of Communications Science, Dr. Soetomo University, 2022)
This study examines communication strategies, especially the East Kalimantan provincial government, in tourism development during the COVID-19 pandemic. This research aims to be a benchmark for other areas affected by COVID-19. It also adds to a better understanding of the current government, stakeholders, and other tourist enterprises’ communication. Understanding communication's underlying structure is also crucial for gaining a competitive edge in a crisis. The type of research used in this research is qualitative. The data collection in this study was in the form of secondary data taken from literature, thirty online media, and the official website of the East Kalimantan provincial government. Data analysis in this study used NVivo 12 Plus software with crosstab query analysis. The result of this research is that the communication strategy of the East Kalimantan provincial government is relatively good. Proven by implementing a communication strategy based on collaboration between institutions and supported by digital media, building converged communication and providing excellent service. The government also uses a marketing communication strategy. However, another finding is that the role obtained in the implications of technology can be a concern in integrating digital media.